2013
DOI: 10.1155/2013/973716
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Inheritance of Scheuermann’s Disease

Abstract: The mode of Scheuermann's disease inheritance and its phenotypic traits in probands and their relatives were studied in 90 pedigrees (90 probands and 385 relatives). The disorder was identified as a genetically related pathology inherited by autosomal dominant type, controlled by a mutant major gene, as a kyphotic deformity without signs of vertebral bodies' anomaly and torsion. Morphological and biochemical studies showed disturbance in the structure of vertebral growth plate anterior aspects at the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…Collagen II is the major collagen of the mature cartilage matrix. It constitutes the structural basis of the chondron and forms a chondrometabolic barrier together with PGs 24. Cartilage PGs perform metabolic, barrier, receptor, and other functions 31, 32.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen II is the major collagen of the mature cartilage matrix. It constitutes the structural basis of the chondron and forms a chondrometabolic barrier together with PGs 24. Cartilage PGs perform metabolic, barrier, receptor, and other functions 31, 32.…”
Section: Resultsmentioning
confidence: 99%
“…Morphology, histochemistry, biochemistry, ultrastructural analysis. Morphological, histochemical, biochemical, and ultrastructural studies of cells and matrix growth plates of the vertebral bodies of patients with IS and of the control samples were performed according to protocols described previously 24.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that patients with AIS or Scheuermann disease have a family history of these diseases, but these patients were not confirmed to be diagnosed with both Sheuermann’ disease and AIS. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…76 The etiology for Scheuermann's disease is multifactorial and complex, with a genetic as well as an environmental contribution. 77 Mechanical stress was also proposed as a contributing factor given its association with athletes and heavy manual labor. 76 Furthermore, experimental studies in young rats showed that repetitive strains produced histologic changes in end plates similar to that seen in Scheuermann's disease: disorganized endochondral ossification replaced by disorganized clumps of chondrocytes.…”
Section: Scheuermann's Diseasementioning
confidence: 99%
“…84 The degree of thoracic kyphosis required to make the diagnosis also fluctuates between 35 and 45 degrees, 85 with kyphosis as low as 25 degrees accepted. 77 A variant of Scheuermann's disease is also recognized, but confusingly has been called several names including lumbar, thoracolumbar, atypical, or type II Scheuermann's. [86][87][88] Lumbar Scheuermann's is also linked with athletic adolescents and is seen in sports including weightlifting, cheerleading, gymnastics, and skiing.…”
Section: Scheuermann's Diseasementioning
confidence: 99%